2014
DOI: 10.1155/2014/403893
|View full text |Cite
|
Sign up to set email alerts
|

The Filtering of the Posturographic Signals Shows the Age Related Features

Abstract: Objective. Lower frequencies of slow oscillations of the posturographic signals can be removed using high-pass filtering. This procedure releases postural reflexes possessing higher frequencies and lower amplitude range. Mutual dependence between the x and y components of posturographic signals was analyzed using principal component analysis (PCA). The posturographic signals of old patients with idiopathic gait disturbance were compared with the control group of similar age and with younger patients. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…According to the results of the present study, the patients with and without self-report KI differed regarding the indicators of the dynamic balance state with closed eyes, which is in line with the previous findings in this regard, which have demonstrated that vision plays a pivotal role in maintaining balance [29]. In addition to the present study, this phenomenon has been confirmed in patients with osteoarthritis in a previous research conducted by Truszczyńska-Baszak et al who limited the vision of KOA patients and observed that their postural control severely reduced, and training was required to maintain their balance control [30].…”
Section: Discussionsupporting
confidence: 92%
“…According to the results of the present study, the patients with and without self-report KI differed regarding the indicators of the dynamic balance state with closed eyes, which is in line with the previous findings in this regard, which have demonstrated that vision plays a pivotal role in maintaining balance [29]. In addition to the present study, this phenomenon has been confirmed in patients with osteoarthritis in a previous research conducted by Truszczyńska-Baszak et al who limited the vision of KOA patients and observed that their postural control severely reduced, and training was required to maintain their balance control [30].…”
Section: Discussionsupporting
confidence: 92%
“…The data obtained here confirms the earlier findings 17,21,40–44 that visual signals are crucial for control of body balance. The rate of stabilisation was higher, and stabilisation time longer when the eyes were closed compared with open eye conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to other organs, the human postural control system undergoes the ageing process [20, 21]. Young persons are able to perform balance with relative good efficiency even when excluding visual and vestibular input and while performing mental tasks which reduce the influence of conscious attention.…”
Section: Introductionmentioning
confidence: 99%